Hungary’s image on the international capital markets - causes and consequences - Bod, Péter Ákos (The Hungarian Journal of Marketing and Management, 2019)
The author reviews the factors, agents and shapers of the external image of the Hungarian economy, and determines that Hungary’s foreign image has significantly deteriorated since the mid-2000s according to comparative international rankings and indices, particularly due to the excessive size of the public sector, its inefficiency and lack of transparency. Since the eruption of the international financial turbulences in 2007/08, the community of the international financial analysts, and particularly the major rating agencies that provide sovereign risk ratings, has emerged as the critical shaper of Hungary’s external image. The conclusion of the paper is that in order to correct the recent negative trend in country perception, Hungary must keep on reducing budget deficit and should also declare convincingly her conservative fiscal stance both domestically and externally.